The Debate on Islamist Party Formation: A Comparative Analysis of al-Būtī and al-Qaradāwī (Perdebatan tentang pembentukan parti islam: analisa per-bandingan antara albuti dan alqardhawi) - Bakour, Bachar (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
Abstract The paper examines the debate over the legal position of Islamist party formation through comparing views of two preeminent Muslim thinkers: M.S.R al-Būtī (antagonist) and Yūsuf al-Qaradāwī (protagonist). Using a text-by-text scheme, the paper tests the validity of the cited textual evidences on the basis of the primary sources of Sharī‘a and the experience of today’s Islamists: the Muslim Brotherhood (parent organization), Hizb al-Tahrīr, and the Justice and Development Party (AKP). Finally, the paper contends that Islamist parties are a system, accredited by Islamic principles, and a reality imposed by changing circumstances of Muslim nations in history, culture, and politics. Keywords: al-Būtī, al-Qaradāwī, Islamist, party, political, formation, the Muslim Brotherhood. Abstrak Kertas ini membincangkan kedudukan pembentukan parti-parti Islam dengan membandingkan pandangan dua cendiakawan Muslim terkemuka iaitu: M.S.R al-Būtī (antagonis) dan Yūsuf al-Qaradāwī (protagonis). Dengan menggunakan skema ayat dengan ayat, kertas ini mengkaji kesahihan bukti teks yang dirujuk berdasarkan Sharī'a dan pengalaman para Islamis pada hari ini seperti Ikhwanul Muslimin (organisasi induk), Hizb al-Tahrīr, dan Parti Keadilan dan Pembangunan (AKP). Akhirnya, kertas ini menyimpulkan bahawa parti-parti Islam adalah satu sistem, yang berlandaskan prinsip-prinsip Islam, dan juga satu kenyataan yang dikenakan oleh perubahan keadaan negara-negara Islam dalam sejarah, budaya, dan politik. Kata Kunci: al-Būtī, al-Qaradāwī, Islam, pesta, politik, pembentukan, Ikhwanul Muslimin.